La honda bilingüe lectora: building a bilingual ecosystem through social work in a rural community of Pereira (2021)
This didactic sequence aims to describe the impact of creating a bilingual ecosystem in the rural community of La Honda through social work, mediated by Content and Language Integrated Learning (CLIL) approach. La Honda Bilingüe Lectora is one of five English workshops whose target population are fifth graders from La Honda school, located in Combia Baja, Pereira, Colombial. In addition, all La Honda Bilingüe projects were created in response to the community’s desire to learn English as rural locations lack governmental support and socio-economic resources (Bonilla & Cruz-Arcila, 2013). As a result, eleven learning experience sessions were developed to expose children to literature to foster interaction and communication, following the guidelines and methodology of Escuela Nueva model suggested by Ministerio de Educación Nacional (MEN). Through the process of creation and development of this project, have arised some meaningful conclusions in terms of lesson planning, children literature and rural teaching awareness which will be detailed addressed in conclusions, limitations and implications sections.